2007
DOI: 10.1038/labinvest.3700502
|View full text |Cite
|
Sign up to set email alerts
|

Roles of coagulation pathway and factor Xa in rat mesangioproliferative glomerulonephritis

Abstract: Tissue factor initiates the extrinsic coagulation pathway by activating coagulation factor X to factor Xa, and factor V is a cofactor for the prothrombin activation by factor Xa. As factor Xa is known to promote the proliferation of mesangial cells in culture, the roles of the coagulation pathway and factor Xa were studied in an animal model of mesangioproliferative glomerulonephritis (MsPGN). MsPGN was induced in Wistar rats by an intravenous injection of anti-Thy 1.1 monoclonal antibody, OX-7. To clarify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Importantly, specific FXa inhibition is beneficial in rat model of mesangioproliferative glomerulonephritis, in part by reducing fibrin deposition. 37 We recently showed FXa stimulated fibroblast proliferation, differentiation into myofibroblast and the expression of profibrotic proteins via PAR-2 activation. 13 Next to a direct role on fibroblast activation during pulmonary fibrosis, PAR-2 activation may well aggravate fibrosis by modulating epithelial barrier functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, specific FXa inhibition is beneficial in rat model of mesangioproliferative glomerulonephritis, in part by reducing fibrin deposition. 37 We recently showed FXa stimulated fibroblast proliferation, differentiation into myofibroblast and the expression of profibrotic proteins via PAR-2 activation. 13 Next to a direct role on fibroblast activation during pulmonary fibrosis, PAR-2 activation may well aggravate fibrosis by modulating epithelial barrier functions.…”
Section: Discussionmentioning
confidence: 99%
“…56 Further support for an important role of FXa-PAR-2 in fibrosis is derived from a rat model of mesangioproliferative glomerulonephritis showing that both FXa and PAR-2 are overexpressed and that specific FXa inhibition is beneficial. 37 Moreover, a recent clinical study shows that Dalteparin (a FXa inhibitor) administration improved the survival of IPF patients. 58 Because, to date, no PAR-2 antagonists are clinically available, the inhibition of FXa might be an interesting alternative therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…PAR2 is activated by TF-coagulation factor VIIa complex and coagulation factor Xa (FXa) and upregulates inflammation and fibrosis through nuclear factor-kappa B (NF-κB) or mitogenactivated protein kinase (MAPK) signaling. [12][13][14] Although FXa and PAR2 are suggested to be responsible for the progression of kidney injury, [15][16][17][18] their role in DN is poorly understood.…”
mentioning
confidence: 99%
“…Biochemical measurements 16 Urinary albumin levels were determined using the Albuwell-M kit (Exocell Inc., Philadelphia,…”
mentioning
confidence: 99%
“…14,15) We previously reported that the coagulation process proceeds together with the ECM accumulation through factor V expression in rat Thy-1 nephritis, 16) and that DX-9065a, a factor Xa inhibitor, suppresses this type of gomerulonephritis. 17) Because renal tissue factor expression and fibrin deposition are observed in streptozotocin-induced type 1 diabetic mice, 5,18) it is suspected that the coagulation process is activated through factor Xa formation in diabetic nephropathy. It has been reported that fondaparinux, a synthetic pentasaccharide that selectively inhibits factor Xa, reduces the inflammatory response in injured kidneys due to ischemia-reperfusion.…”
mentioning
confidence: 99%